Isolation of mosquito larvicidal molecule form the leaves of Clausena anista - Jayaraman, M.; Senthilkumar, A.; Adaikala Raj, G.; Venkatesalu, V. (Journal of Experimental Sciences, 2015)
The vector-borne diseases caused by mosquitoes are one of the major health problems in many countries especially in tropical and sub-tropical countries. The resistance of mosquitoes to synthetic chemicals and environmental toxicity created by the chemicals raised the demand for finding of alternate natural molecules that control mosquito. In the present study, the compound 1, 2-Benzenedicarboxylic acid, mono (2-ethylhexyl) ester was isolated from the ethyl acetate extract of leaves of Clausena anisata and it was identified by various spectral studies. The larvicidal potential of the isolated compound was evaluated against early 4th instar larvae of Culex quinquefasciatus, Aedes aegypti and Anopheles stephensi. The compound exhibited 100% larval mortality against A. aegypti and A. stephensi at 40 ppm with LC50 values of 8.944 and 9.230 ppm respectively. The molecule also showed the LC50 value of 12.067 ppm against C. quinquefasciatus. The molecule isolated from C. anisata can be better explored for the control of mosquito population after toxicological evaluation.